2011
DOI: 10.1212/wnl.0b013e318203e952
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic disparities in access to physician care and medications among US stroke survivors

Abstract: Background: Mexican Americans and non-Hispanic blacks have higher stroke recurrence rates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 38 publications
0
36
1
Order By: Relevance
“…46 Lower health literacy, denial of disease, concern for potential or experienced side effects of medications, absence of symptoms, burden of filling prescriptions, and perceived racial bias from the healthcare system may influence receipt of and compliance with treatment. 46 Among older stroke survivors, blacks and Mexican Americans reported poorer access to medications and physician care than whites, potentially leading to inadequate risk factor modification and recurrent events in these high-risk minority groups, 46,[50][51][52][53] although differences are attenuated after adjustment for age, sex, education, and insurance status. 51 Potential causes for these disparities include differences in socioeconomic status, healthcare access and use, and availability of community resources.…”
Section: Strokementioning
confidence: 99%
“…46 Lower health literacy, denial of disease, concern for potential or experienced side effects of medications, absence of symptoms, burden of filling prescriptions, and perceived racial bias from the healthcare system may influence receipt of and compliance with treatment. 46 Among older stroke survivors, blacks and Mexican Americans reported poorer access to medications and physician care than whites, potentially leading to inadequate risk factor modification and recurrent events in these high-risk minority groups, 46,[50][51][52][53] although differences are attenuated after adjustment for age, sex, education, and insurance status. 51 Potential causes for these disparities include differences in socioeconomic status, healthcare access and use, and availability of community resources.…”
Section: Strokementioning
confidence: 99%
“…198 A recent analysis of 4864 stroke survivors Ն45 years of age who responded to the National Health Interview Survey in 2000 to 2006 revealed that Mexican Americans and blacks or African Americans Ն65 years of age had reduced access to primary care providers and were less able to afford medications when compared with whites. 199 There was no difference in access to primary care providers or medications among those Ͻ65 years of age. However, Mexican Americans and blacks or African Americans in any age group had worse access to evaluation by specialists.…”
Section: Disparities In Preventionmentioning
confidence: 92%
“…78 Indeed, in the National Health Interview Survey for the years 2000 through 2006, of 4864 stroke survivors >65 years of age, Mexican Americans and non-Hispanic blacks reported a lower proportion of specialist visits compared with non-Hispanic whites. 79 …”
Section: Approachabilitymentioning
confidence: 99%